Evaluation of Total Hardness and Qualitative Analysis of Boiler Water at the Food Jam Industry, Tangerang, Indonesia - Satrio Kuntolaksono; Imam Wicaksono; Febrianty Emilia; Enjarlis Enjarlis; Linda Aliffia Yoshi (BIORE Scientia Publisher, 2022)
Food industry is one of the most crucial and rapidly growing economic sectors in Indonesia. One of the examples is the food jam industry. This industry was located in Tangerang, Indonesia. The majority of the food jam industry uses its own source of water, so this part is also important to water producers in Indonesia. Water used in the food jam industry should meet the requirements of at least drinking water quality, so the factories need to treat the water. Good quality water is water that requires good physical, chemical, and bacteriology properties. Hard water is a term known for water that contains a high concentration of minerals such as Calcium (Ca) and Mag-nesium (Mg). Moreover, water with very high degrees of hardness is harmful to health. In this study, we want to evaluate and determine the pH, total hardness, and total dissolved solids (TDS) at three different times namely morning, midday, and afternoon. The results obtained in the range of pH analysis are 6.98 to 7.99 with all cover times. The total hardness in the boiler water and the TDS are around 252.6 to 388.2 mg/L and 310 to 406 mg/L, respectively. These results indicated that it has fulfilled the requirements for total hardness values under the Minister of Health Regulations (Permenkes) No. 492/Menkes/Per/IV/2010.